2013
DOI: 10.1016/j.cub.2013.06.022
|View full text |Cite
|
Sign up to set email alerts
|

Frequency-Dependent Enhancement of Fluid Intelligence Induced by Transcranial Oscillatory Potentials

Abstract: Everyday problem solving requires the ability to go beyond experience by efficiently encoding and manipulating new information, i.e., fluid intelligence (Gf) [1]. Performance in tasks involving Gf, such as logical and abstract reasoning, has been shown to rely on distributed neural networks, with a crucial role played by prefrontal regions [2]. Synchronization of neuronal activity in the gamma band is a ubiquitous phenomenon within the brain; however, no evidence of its causal involvement in cognition exists t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

7
144
0

Year Published

2014
2014
2024
2024

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 189 publications
(152 citation statements)
references
References 41 publications
7
144
0
Order By: Relevance
“…Previous in vitro and in vivo studies have only shown acute effects of stimulation on oscillatory activity (Reato et al 2010;Fröhlich and McCormick 2010;Ali et al 2013;Ozen et al 2010), and there are few reports on longer term effects in human studies (see Antal et al 2004;Polanía et al 2011). The majority of studies on oscillatory activity have used alternating current stimulation with the goal of enhancing brain oscillations (Marshall et al 2006;Pogosyan et al 2009;Kirov et al 2009;Zaehle et al 2010;Santarnecchi et al 2013;Helfrich et al 2014). …”
Section: Discussionmentioning
confidence: 99%
“…Previous in vitro and in vivo studies have only shown acute effects of stimulation on oscillatory activity (Reato et al 2010;Fröhlich and McCormick 2010;Ali et al 2013;Ozen et al 2010), and there are few reports on longer term effects in human studies (see Antal et al 2004;Polanía et al 2011). The majority of studies on oscillatory activity have used alternating current stimulation with the goal of enhancing brain oscillations (Marshall et al 2006;Pogosyan et al 2009;Kirov et al 2009;Zaehle et al 2010;Santarnecchi et al 2013;Helfrich et al 2014). …”
Section: Discussionmentioning
confidence: 99%
“…In detail, cathodal tDCS improves task performance when applied during the early acquisition phase, probably due to its reducing effect on distractive cortical noise, whereas anodal stimulation improves performance when applied in the later stages, presumably via its activity-enhancing effect on task-related neuronal activity [50] . It has been suggested that prefrontal gamma activity is relevant for performance of this kind of task, and indeed tACS in the gamma frequency range seems to improve fl uid intelligence [51] .…”
Section: Problem-solvingmentioning
confidence: 99%
“…Various protocols have shown benefits in domains such as working and longterm memory (Javadi and Cheng 2013;Mulquiney et al 2011), fluid reasoning (Santarnecchi et al 2013), task switching (Leite et al 2013), language learning (Flöel et al 2008), positive mood (Austin et al 2016) and learning complex sensori-motor tasks (Choe et al 2016). It is reasonably well established that NIBS offers a modest boost to performance in many tasks.…”
Section: Non-invasive Stimulation In Enhancing Cognitionmentioning
confidence: 99%